Higher levels of narrativity lead to similar patterns of posterior EEG activity across individuals - Dini, Hossein; Simonetti, Aline; Bigne, Enrique; Bruni, Luis Emilio (Frontiers in Human Neuroscience, 2023)
The focus of cognitive and psychological approaches to narrative has not so much been on the elucidation of important aspects of narrative, but rather on using narratives as tools for the investigation of higher order cognitive processes elicited by narratives (e.g., understanding, empathy, etc.). In this study, we work toward a scalar model of narrativity, which can provide testable criteria for selecting and classifying communication forms in their level of narrativity. We investigated whether being exposed to videos with different levels of narrativity modulates shared neural responses, measured by inter-subject correlation, and engagement levels. Thirty-two participants watched video advertisements with high-level and low-level of narrativity while their neural responses were measured through electroencephalogram. Additionally, participants’ engagement levels were calculated based on the composite of their self-reported attention and immersion scores. Results demonstrated that both calculated inter-subject correlation and engagement scores for high-level video ads were significantly higher than those for low-level, suggesting that narrativity levels modulate inter-subject correlation and engagement. We believe that these findings are a step toward the elucidation of the viewers’ way of processing and understanding a given communication artifact as a function of the narrative qualities expressed by the level of narrativity.